Implementasi Desa Zakat Kabupaten Serdang Bedagai Sumatera Utara dengan Pendekatan Indeks Desa Zakat 2.0 - Isnaini Harahap; Yenni Samri Nasution; Suherman Saragih (ITB AAS INDONESIA Surakarta, 2022)
Contribution of zakat can be further felt by the people who are assisted directly throughout Indonesia which is indirectly related to indonesia's more empowered human development but based on the report of IZN Puskas Baznas 2020 that Organiasai Zakat Manager (OPZ) Serdang Bedagai Regency does not fill the IZN and Impact Assessment so as to describe the conditions in OPZ Serdang Bedagai which is